2022
DOI: 10.1016/j.csbj.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

LCMD: Lung Cancer Metabolome Database

Abstract: Lung cancer, one of the most common causes of cancer-related death worldwide, has been associated with high treatment cost and imposed great burdens. The 5-year postoperative survival rate of lung cancer (13%) is lower than many other leading cancers indicating the urgent needs to dissect its pathogenic mechanisms and discover specific biomarkers. Although several proteins have been proposed to be potential candidates for the diagnosis of lung cancer, they present low accuracy in clinical settings. Metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Genome Sequence Archive (GSA) ( 278 ) developed by the Chinese National Genomic Data Center has been launched to compliment this giant-size database portfolio, with GSA-human recently announced as part of GSA to provide a repository for human genetic related omics data ( 279 ). Various databases smaller in size and/or with more specialized focuses have been established by different groups such as “LCMD” for lung cancer metabolome ( 280 ), “DBSAV” for deleterious single amino acid variation prediction in human proteome ( 281 ), “SARS-CoV-2 3D” for coronavirus proteome ( 282 ), and “CMVdb” for cytomegalovirus multi-omes ( 283 ). A plethora of machine-learning algorithms and computational tools have been developed to interrogate these omics data toward gained knowledge or new discoveries such as WeiBI for PPI taking into account of functional enrichment ( 284 ), DTI-MLCD for drug-target interactions utilizing multi-label learning ( 285 ), and MDF-SA-DDI for predicting interaction events between two drugs based on a transformer self-attention mechanism ( 286 ).…”
Section: Trends In Omics Technology Developmentmentioning
confidence: 99%
“…Genome Sequence Archive (GSA) ( 278 ) developed by the Chinese National Genomic Data Center has been launched to compliment this giant-size database portfolio, with GSA-human recently announced as part of GSA to provide a repository for human genetic related omics data ( 279 ). Various databases smaller in size and/or with more specialized focuses have been established by different groups such as “LCMD” for lung cancer metabolome ( 280 ), “DBSAV” for deleterious single amino acid variation prediction in human proteome ( 281 ), “SARS-CoV-2 3D” for coronavirus proteome ( 282 ), and “CMVdb” for cytomegalovirus multi-omes ( 283 ). A plethora of machine-learning algorithms and computational tools have been developed to interrogate these omics data toward gained knowledge or new discoveries such as WeiBI for PPI taking into account of functional enrichment ( 284 ), DTI-MLCD for drug-target interactions utilizing multi-label learning ( 285 ), and MDF-SA-DDI for predicting interaction events between two drugs based on a transformer self-attention mechanism ( 286 ).…”
Section: Trends In Omics Technology Developmentmentioning
confidence: 99%
“…Various HRMS-based untargeted metabolomics strategies for biomarker discovery have been developed and proposed, such as a combination of full-scan and targeted MS/MS, data-dependent acquisition (DDA), and data-independent acquisition (DIA). For example, 26 papers reported the use of the HRMS-based untargeted metabolomics strategy to discover lung cancer biomarkers, as shown in Table S1 . Among these, it was reported that a full scan with targeted MS/MS was performed in 17 papers, DDA mode was utilized in eight papers, and DIA mode was used in one paper.…”
Section: Introductionmentioning
confidence: 99%
“…24−27 For example, 26 papers reported the use of the HRMS-based untargeted metabolomics strategy to discover lung cancer biomarkers, as shown in Table S1. 28 Among these, it was reported that a full scan with targeted MS/MS was performed in 17 papers, DDA mode was utilized in eight papers, and DIA mode was used in one paper. The combination procedure was performed using the full scan method to obtain metabolic signals in the individual biological samples, including abundance, accurate m/z, and retention time.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some clinical research attempts to optimize lung cancer diagnosis by searching for the metabolites associated with the disease incidence, using state-of-the-art facilities in molecular biology [ 16 21 ]. Over 2000 metabolites have been profiled in various specimens (e.g., sera, plasma, and tissues) derived from lung cancer patients [ 21 ], while very few of them are identified statistically as lung cancer biomarkers [ 16 21 ]. To date, over 600 metabolites remain unknown for their classification and roles in lung cancer metabolism [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 2000 metabolites have been profiled in various specimens (e.g., sera, plasma, and tissues) derived from lung cancer patients [ 21 ], while very few of them are identified statistically as lung cancer biomarkers [ 16 21 ]. To date, over 600 metabolites remain unknown for their classification and roles in lung cancer metabolism [ 21 ]. Only a few studies unveil the metabolic alterations associated with anoikis resistance, such as elevations in glycolysis, asparagine bioavailability, and fatty acid uptake [ 22 ].…”
Section: Introductionmentioning
confidence: 99%